BETWEEN REFLECTION AND ACTION: POSTPONEMENT OF RETIREMENT AND INCIPIENT PREPARATION AMONG TECHNICAL-ADMINISTRATIVE STAFF AGED 60+ AT A FEDERAL UNIVERSITY - Silva, Regiane Vieira; Martins, Simone; Vaccaro, Stefania Becattini; Fernández, Alejandro Pérez-Duarte; Calderano, Josieli Moris Gomes (Seven Editora, 2026)
This article presents the results of a study investigating how technical-administrative staff in education at a public university perceive and prepare for retirement, as well as how the institution contributes to this process. The theoretical framework is based on the Transtheoretical Model of Behavior Change, by Prochaska and DiClemente (1983), used as an analytical lens to understand the different positions of employees regarding the decision to retire. A qualitative approach was adopted, involving 76 semi-structured interviews and two focus groups, with eight participants each, whose data were analyzed using the content analysis technique (Bardin, 2011). The results indicate that continued employment is sustained by fear of idleness and loss of an active routine, concern about the disruption of social ties, and threats to professional identity, positioning work as the central axis of daily life and institutional belonging. Low preparation for retirement and the absence of structured institutional policies are also evidenced, factors that contribute to insecurity and the postponement of the decision to leave work. It is concluded that retirement is experienced in an ambivalent manner, marked by insecurity, low readiness, and postponement of the decision, aggravated by the absence of structured institutional support. The study contributes to the academic debate on aging, work, and human resource management in the public sector, in addition to offering support for reflection on institutional policies to support the transition from work to retirement in the context of public universities.DOI: https://doi.org/10.56238/sevened2026.008-119